Psychoanalysis and Philosophy of Mind. - Boag, Simon (Karnac Books, 2015)
Of the topics found in psychoanalytic theory it is Freud's philosophy of mind that is at once the most contentious and enduring. Psychoanalytic theory makes bold claims about the significance of unconscious mental processes and the wish-fulfilling activity of the mind, citing their importance for understanding the nature of dreams and explaining both normal and pathological behaviour. However, since Freud's initial work, both modern psychology and philosophy have had much to say about the merits of Freudian thinking. Developments in psychology, philosophy, and psychoanalysis raise new challenges and questions concerning Freud's theory of mind. This book addresses the psychoanalytic concept of mind in the 21st century via a joint scientific and philosophical appraisal of psychoanalytic theory. It provides a fresh critical appraisal and reflection on Freudian concepts, as well as addressing how current evidence and scientific thinking bear upon Freudian theory. The book centres upon the major concepts in psychoanalysis, including the notion of unconscious mental processes and wish-fulfilment and their relationship to dreams, fantasy, attachment processes, and neuroscience.